ARTIFICIAL NATURE: SYMBIOTIC RELATIONS OF BUILT-FORM AND NATURE IN THE POST-ANTHROPOCENE ARCHITECTURE - Ariko Andikabina; Gita Rahma Mathilda; Yandi Andri Yatmo; Kristanti Dewi Paramita (Journal of Architecture & Environment, 2026)
This study aims to demonstrate a design transformation that demonstrates symbiotic relationship between built-form and nature with the overarching objective of fostering ecological sustainability in the emerging post-Anthropocene epoch. This study can be considered as a direct response to current architectural paradigms that predominantly prioritize human needs and requirements, often at the expense of environmental well-being. Most of our built environment stands on the modes of resource extraction and consumption, frequently relying on finite, non-renewable materials, generating substantial pollutants that disrupt delicate ecological equilibrium. This study begins by exploring the idea of symbiotic between architecture and nature in current design discourse. The exploratory design study follows by establishing potential natural elements that can be accommodated within built-form as living systems. The study identifies three specific roles in the environment as part of the symbiotic programming, which are to feed, to fuel, and to heal. This speculative study further develops architecture proposition as a form of artificial nature through connections of these different programs. By exploring mutually beneficial symbiotic relationships between built-form and natural elements, the study found that artificial nature can create interdependent outputs, where outcomes from feeding can be used for either healing or fueling, and vice versa. This study highlights the need to create architecture that transforms and unfolds as open and collaborative systems. Such discussion informs a systemic form of architecture, where its spatiality enables growth of biological organisms that metabolize the spatial process and its surroundings.